Tata Kelola Perusahaan, Kinerja Keuangan, dan Penghindaran Pajak: Studi Pada Sub Sektor Makanan dan Minuman (2022–2024) - Widia Octari Diliana; Eve Ida Malau; Anindya Septisuwendani; Hardo Aprilio (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to analyze the effect of corporate governance and financial performance on tax avoidance in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Corporate governance is measured using the proportion of independent commissioners and audit committees, while financial performance is proxied by Return on Assets (ROA). The study uses a quantitative approach with a purposive sampling technique, resulting in 30 companies as the sample with a total of 90 observations. Data analysis is conducted through multiple linear regression and is complemented by classical assumption tests to ensure that the model meets statistical requirements. The results show that independent commissioners have no effect on tax avoidance, while audit committees and ROA have a significant effect on tax avoidance. Simultaneously, the three independent variables are proven to influence tax avoidance. These findings provide the latest empirical evidence regarding the role of corporate governance and profitability in influencing tax avoidance in the food and beverage sub-sector and are expected to serve as a consideration for stakeholders in improving tax transparency, oversight, and compliance.